Situational Analysis of Shallot Supply Chain Innovation System: A Case Study of Majalengka-Indonesia - Wahyu Trisnasari; Marimin Marimin; Tomy Perdana; Yosini Deliana (International Journal of Supply Chain Management, 2020)
Situational analysis is an important study to understand the root causes and solutions that are relevant to a phenomenon. The research focused on the situational analysis of the shallot supply chain which encountered problems of production and downstream instability, which affected inflation and deflation. Without a clear situational analysis, institutional intervention becomes more difficult. The aim of the study was to analyze the situation of the shallot supply chain case study in Majalengka Regency, Indonesia. Situational analysis is carried out using a soft system dynamic methodology (SSDM) approach. The research produced a picture of the real world supply chain of shallots through a rich picture chart. Relevant systems that will be built are obtained through CATWOE analysis including; support system for fulfilling irrigation production infrastructure to ensure production stability; sustainable guidance system for independent seed production; special institutional systems which function as absorbent products, guarantor of product quality standards and regulator of price stability; a system that provides training to increase product added value in a sustainable manner as well as training for institutional farming development; and a system that provides GAP training to ensure the quality and quantity of products leading to a structured market. The relationship in the pictured system is illustrated through a causal loop diagram (CLD) chart. The next step that can be done from the results of the research is analyzing the behavior of the model and developing a scenario to improve policies that can support the development of innovation systems in the shallot supply chain. Keywords: Innovation system, Production and downstream, Supply chain, Soft system dynamics methodology